Simplifying
9x + -7i = 3(3x + 7u)
Reorder the terms:
-7i + 9x = 3(3x + 7u)
Reorder the terms:
-7i + 9x = 3(7u + 3x)
-7i + 9x = (7u * 3 + 3x * 3)
-7i + 9x = (21u + 9x)
Add '-9x' to each side of the equation.
-7i + 9x + -9x = 21u + 9x + -9x
Combine like terms: 9x + -9x = 0
-7i + 0 = 21u + 9x + -9x
-7i = 21u + 9x + -9x
Combine like terms: 9x + -9x = 0
-7i = 21u + 0
-7i = 21u
Solving
-7i = 21u
Move all terms containing i to the left, all other terms to the right.
Divide each side by '-7'.
i = -3u
Simplifying
i = -3u